The Concept of Al-Qur’an and Islamic Law in Educating Wife and The Solution for Dispute Settlement in Household Violence - Asep Habib Idrus Alawi (UIN Sunan Gunung Djati Bandung, 2018)
The obligation to give a lesson to the wife is if he starts disobeying and shows nusyuz to his husband. So the husband is obliged to provide lessons, but giving the lesson is carried out in sequence, the first husband must give a warning to the wife gently and subtly like reminding him to fear Allah Almighty, if the wife is obedient again, then just enough there. If it still remains disobedient, then leave the wife alone, leaving her on the bed, not collecting it, especially when her lust peaks. If he is obedient, then it is enough to get there and gather the wife as before. But if it remains, the wife may be 'beaten' with a note not too loud and not injured.